By Regulating Mitochondrial Ca2+-Uptake UCP2 Modulates Intracellular Ca2+. - Lukas Jaroslaw Motloch; Robert Larbig; Tina Gebing; Sara Reda; Astrid Schwaiger; Johannes Leitner; Martin Wolny; Lars Eckardt; Uta C Hoppe (PLoS ONE, 2016)
The possible role of UCP2 in modulating mitochondrial Ca2+-uptake (mCa2+-uptake) via the mitochondrial calcium uniporter (MCU) is highly controversial.Thus, we analyzed mCa2+-uptake in isolated cardiac mitochondria, MCU single-channel activity in cardiac mitoplasts, dual Ca2+-transients from mitochondrial ((Ca2+)m) and intracellular compartment ((Ca2+)c) in the whole-cell configuration in cardiomyocytes of wild-type (WT) and UCP2-/- mice.Isolated mitochondria showed a Ru360 sensitive mCa2+-uptake, which was significantly decreased in UCP2-/- (229.4±30.8 FU vs. 146.3±23.4 FU, P<0.05). Single-channel registrations confirmed a Ru360 sensitive voltage-gated Ca2+-channel in mitoplasts, i.e. mCa1, showing a reduced single-channel activity in UCP2-/- (Po,total: 0.34±0.05% vs. 0.07±0.01%, P<0.05). In UCP2-/- cardiomyocytes (Ca2+)m was decreased (0.050±0.009 FU vs. 0.021±0.005 FU, P<0.05) while (Ca2+)c was unchanged (0.032±0.002 FU vs. 0.028±0.004 FU, P>0.05) and transsarcolemmal Ca2+-influx was inhibited suggesting a possible compensatory mechanism. Additionally, we observed an inhibitory effect of ATP on mCa2+-uptake in WT mitoplasts and (Ca2+)m of cardiomyocytes leading to an increase of (Ca2+)c while no ATP dependent effect was observed in UCP2-/-.Our results indicate regulatory effects of UCP2 on mCa2+-uptake. Furthermore, we propose, that previously described inhibitory effects on MCU by ATP may be mediated via UCP2 resulting in changes of excitation contraction coupling.